Herman Bavinck dan Literatur Hikmat: Pemakaian Amsal 8:22-31 di dalam Reformed Dogmatics - Novan (STT Reformed Injili Internasional, 2024)
This paper aims to review how Herman Bavinck uses Proverbs 8:22-31 as wisdom literature in Reformed Dogmatics by conducting a literature study through a qualitative-comparative approach. With this approach, the author will discuss the concept of using wisdom literature in Bavinck's systematic theology, especially in Reformed Dogmatics. After that, this paper will discuss a case example of how Bavinck uses Proverbs 8:22-31 in Reformed Dogmatics, especially in the doctrine of the Triune God. The paper concludes that Bavinck is a theologian who can articulate his systematic theology in a contextual and organic way (paying attention to the whole organism of Scripture) with faith that submits to the Bible through the way he uses and appreciates Proverbs 8:22-31 as a genre of wisdom literature according to its context from the Old Testament to the New Testament.